M2 Macrophage Subpopulations in Glomeruli Are Associated With the Deposition of IgG Subclasses and Complements in Primary Membranous Nephropathy - Hu, Wenxue; Li, Guanglan; Lin, Jieshan; Dong, Wei; Yu, Feng; Liu, Wei; Wu, Yanhua; Hao, Wenke; Liang, Xinling (Frontiers in Medicine, 2021)
Objectives: The role of M2 macrophages in the pathogenesis and progression of primary membranous nephropathy (PMN) remains unknown. In this study, we aimed to investigate the relationship between M2 subsets and clinicopathological features of patients with PMN. Methods: A total of 55 patients with PMN confirmed by biopsy were recruited. The clinical and pathological data were recorded, respectively. Immunohistochemistry was used to detect the markers of M2 macrophages, including total macrophages (CD68+), M2a (CD206+), M2b (CD86+) and M2c (CD163+). Results: The numbers of glomerular macrophages, M2a, M2b, and M2c macrophages were 1.83 (1.00, 2.67), 0.65 (0.15, 1.15), 0.67 (0.33, 1.50), and 0.80 (0.05, 2.30) per glomerulus, respectively. Higher number of glomerular macrophages was found in stage II compared with stage III (2.08 vs. 1.16, P = 0.008). These macrophages also were negatively correlated with serum albumin level (r = −0.331, P = 0.014), while positively associated with complement 3 (C3) deposition (r = 0.300, P = 0.026) and the severity of glomerulosclerosis (r = 0.276, P = 0.041). Moreover, glomerular M2a macrophages were significantly correlated with the deposition of C3 (r = 0.300, P = 0.026), immunoglobulin G1 (IgG1) (r = 0.339, P = 0.011), immunoglobulin G2 (IgG2) (r = 0.270, P = 0.046) and immunoglobulin G3 (IgG3) (r = 0.330, P = 0.014) in glomerular basement membrane (GBM). In addition, M2b macrophages were positively associated with IgG1 (r = 0.295, P = 0.029) and IgG2 (r = 0.393, P = 0.003), while M2c macrophages were negatively correlated with complement 4d (C4d) (r = −0.347, P = 0.009) in GBM. Conclusions: Our results showed that M2 macrophage subpopulations in glomeruli are associated with the deposition of IgG subclasses and complements in renal tissue of PMN, which indicate that M2 macrophages may be involved in the pathogenesis and progression of PMN. Moreover, M2a and M2c macrophages might show different tendencies in the pathogenesis of PMN.